DIGITAL LOGISTICS AND MODERN TECHNOLOGIES: THEORETICAL AND LEGAL FOUNDATIONS, INTERNATIONAL EXPERIENCE, REFORMS IN UZBEKISTAN, AND PROSPECTS FOR IMPROVEMENT (World Conference on Social Sciences, Law and Public Policy, 2026)
This thesis examines the theoretical, legal and institutional foundations of digital logistics and modern technologies. It analyzes the role of digital logistics in supply chain management, transport services, customs procedures, e-commerce, cybersecurity, personal data protection and artificial intelligence. The paper compares international doctrine and Uzbek reforms, identifies key deficiencies and proposes policy and legal measures for the development of digital logistics in Uzbekistan.
Keywords: digital logistics, supply chain, e-logistics, e-CMR, e-TIR, e-Permit, e-Freight, electronic document, digital signature, artificial intelligence, Big Data, IoT, blockchain, cybersecurity, Uzbekistan.